Colorectal Carcinoma Affected Patients Are Significantly Poor Responders Against the Oncogenic JC Polyomavirus - Torreggiani, Elena; Bononi, Ilaria; Pietrobon, Silvia; Mazzoni, Elisa; Guerra, Giovanni; Feo, Carlo; Martini, Fernanda; Tognon, Mauro (Frontiers in Immunology, 2021)
Background Many investigations reported the association between human tumors and JCPyV, a polyomavirus with oncogenic potential. The association has been supported by studies that found JCPyV footprints in CRC and gliomas of different types. Indeed, JCPyV footprints including its nucleic acids and Tag oncoprotein have been revealed in CRC tissues. Methods Herein, sera from colorectal carcinoma (CRC) affected patients and healthy individuals (HS), employed as control, were analysed for immunoglobulin G (IgG) antibodies against specific JCPyV viral capsid protein 1 (VP1) antigens. The investigation was carried out employing an innovative immunological assay. Indeed, an indirect enzyme-linked immunosorbent assay (ELISA) with JCPyV VP1 mimotopes was used. JCPyV VP1 mimotopes consisted of synthetic peptides mimicking VP1 epitopes. Results Sera from CRC affected patients, evaluated using indirect ELISAs with synthetic mimotopes, showed a significant lower prevalence of IgG antibodies against JCPyV VP1 mimotopes (26%) compared to HS (51%), p<0.005. These data were confirmed by another method, the hemagglutination inhibition (HAI) assay. Altogether these results, i.e. the prevalence of serum IgG antibodies against JCPyV VP1 mimotopes from patients with CRC is approximately 50% lower than in HS, are of interest. Discussion Our data suggest that patients with CRC are significantly poor responders against JCPyV VP1 antigens. It is possible that CRC patients are affected by a specific immunological deregulation. This immunological dysfunction, revelled in CRC patients, may account for their predisposition to the colorectal carcinoma onset.